2014
DOI: 10.1902/jop.2013.130502
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy Obesity and Periodontitis Among Pregnant Females With and Without Gestational Diabetes Mellitus

Abstract: There is a positive association between prepregnancy obesity and periodontitis among pregnant females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 60 publications
1
29
2
3
Order By: Relevance
“…The findings of the present study did not show an association between obesity in pregnant women and periodontitis after adjustment for probable confounding covariables, contrary to previous studies that found a positive association . Given the paucity of research on this topic, the findings presented in this study deserve to be carefully discussed and compared to those previously published.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the present study did not show an association between obesity in pregnant women and periodontitis after adjustment for probable confounding covariables, contrary to previous studies that found a positive association . Given the paucity of research on this topic, the findings presented in this study deserve to be carefully discussed and compared to those previously published.…”
Section: Discussioncontrasting
confidence: 99%
“…Some previous studies have reported a positive association between excessive weight and periodontitis during pregnancy. Nonetheless, these studies used different methodologies for the classification of periodontitis and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with Neuman et al who identified a lower occupational status limiting the use of dental services. 21 On oral examination, 20.5% of the patients had poor oral hygiene. This suggests that periodontitis is associated with poor oral hygiene.…”
Section: Discussionmentioning
confidence: 99%